Roots of Polynomials

Algebra Level 2

If a x 3 + b x c ax^{3} + bx - c is exactly divisible by x 2 + b x + c x^{2} + bx + c , then find the value of ab.


The answer is 1.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Kartik Jay
Sep 2, 2017

Let p ( x ) = a x 3 + b x c p(x) = ax^{3} + bx - c Let g ( x ) = x 2 + b x + c g(x) = x^{2} + bx + c Now, when forming the polynomial g(x) , the constant was k = 1 But putting k = a will not change g(x)'s roots => g ( x ) = a ( x 2 + b x + c ) g(x) = a(x^{2} + bx + c ) => g ( x ) = a x 2 + a b x + a c g(x) = ax^{2} + abx + ac

Now dividing p(x) by g(x) will give us q ( x ) = x b q(x) = x-b And p(x) divided by q(x) will give us g(x). But while taking the quotient we find that we get g ( x ) = a x 2 + a b x + b ( a b + 1 ) g(x) = ax^{2} + abx + b(ab + 1) and remainder = b 2 ( a b + 1 ) c = 0 b^{2}(ab +1) - c = 0 Equating the two expressions of g(x) we get b ( a b + 1 ) = a c ( 1 ) b(ab+1)=ac -----(1) From remainder; b 2 ( a b + 1 ) c = 0 b^{2}(ab+1) - c = 0 => b × b ( a b + 1 ) = c b×b(ab+1) = c => b × a c = c f r o m ( 1 ) b×ac = c from (1) => a b = 1 ab =1 Q.E.D

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...